ANG IDIOMA’T RETORIKA NG SUGBOANON AT REHIYONAL SA PANITIKANG MINDANAW - Quintos, Jay Jomar F. (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
This essay probes the personal and political doings of curating and teaching a course on Sugboanon literature focused on Mindanaw. Furthermore, it interrogates “regional hegemony” ensconced in the literary institutions and establishments in the peripheral of the nation’s periphery.